Simultaneous Damage of the Cingulate Cortex Zone II and Fronto-Striatal Circuit Causes Prolonged Selective Attentional Deficits - Nakajima, Riho; Kinoshita, Masashi; Nakada, Mitsutoshi (Frontiers in Human Neuroscience, 2021)
Selective attention is essential for successful cognitive performance. Although several brain areas are known to be involved in selective attention, damage to some of these areas does not necessarily cause attentional deficits. In the current study, we hypothesized that damage to specific parts of the right cerebral hemisphere, especially the cingulate cortex (CC), causes prolonged selective attentional deficits, and examined the influence of focal brain damage on selective attention. We recruited 36 patients with right cerebral hemispheric WHO grade 2 and 3 brain tumors who underwent surgery. We assessed selective attention over time from pre-operation to 3 months postoperatively using the cancelation test and color Stroop test, and calculated the percentage of deficit. Additionally, two types of imaging analyses were performed: voxel-based lesion symptom mapping (VLSM) and multiple logistic regression analysis, to reveal related brain regions for selective attention. Consequently, we found that the CC and deep part of the middle frontal gyrus were associated with deficits in selective attention via VLSM. Using multiple logistic regression analysis, the CC zone II at the cortical level (p < 0.0001) and the fronto-striatal tract (FST) at the subcortical level (p = 0.0079) were associated with attentional deficit among several regions identified in the VLSM. At 3 months postoperatively, selective attention was impaired in patients who underwent resection of these regions. Moreover, only patients with simultaneous damage of the CC zone II and FST had prolonged attentional deficits until the chronic phase. Our results suggest that the right CC zone II and FST are critical areas for the selective attentional networks.